GAGASAN POLITIK HASAN MUHAMMAD DI TIRO TENTANG NASIONALISME ACEH - Fadhil Ilhamsyah (Jurnal Public Policy, 2018)
This article aims at elaborating the idea of Hasan Muhammad Di Tiro about nationalism in Aceh who become the ideology of the free Aceh Movement (GAM). The thought of nationalism is Hasan Muhammad di Tiro Aceh is a reflection of disappointment against the attitude of the Government of Indonesia in the injustice of natural resource management. The thought of nationalism in Aceh is very in influence by the history of the triumph of the Kingdom of Aceh in the past that then grow awareness of Hasan Muhammad di Tiro formed to fight the National Liberation Front Acheh-Sumatra. Present day Aceh cannot manifest directly thought of nationalism is Hasan Muhammad di Tiro Aceh that is becoming an independent nation. However indirectly, a sense of nationalism that Aceh has grown and continues to persist in the soul of the Acehnese by keeping the peace as well as the meimplementasikan details of the Helsinki Agreement for the creation of prosperity and well-being for the people Aceh as on aspire by Tengku Hasan Muhammad di Tiro. Keywords: Idea, Nationalism, Aceh